Численное исследование динамической устойчивости вязкоупругих ортотропных прямоугольных пластин с переменной жесткостью - Абдикаримов, Р.А.; Верлань, А.Ф.; Горошко, И.О. (Моделювання та інформаційні технології, 2011)
By numerical simulation the dynamic stability of viscoelastic
orthotropic plates with variable stiffness on the basis of the Kirchhoff-Love hypothesis
in the geometrically nonlinear formulation, taking into account the propagation of
elastic waves is investigated. The effects of viscoelastic material properties and plate
thickness variation on the dynamic stability are studied.